ANALISIS MINAT KERJA DAN PROGRAM MAGANG TERHADAP KESIAPAN KERJA (STUDI TERHADAP MAHASISWA STIE INDONESIA BANKING SCHOOL) - Sastra, Muh. Punggawa Rizha; Nuraya, Ahmad Setiawan (Journal of Accounting, Management and Islamic Economics, 2025)
Work readiness is crucial in preparing human resources for the sustainability of the industry, efforts need to be made to obtain optimal results, in order to improve the research, the objects used as research materials are students of STIE Indonesia Banking School batch 2019 and 2020, with the title of the research "Analysis of the Influence of Work Interest and Internship Programs on Work Readiness" aims to analyze field facts regarding the influence of work interest on work readiness and the influence of internship programs on student work readiness. This research uses a quantitative method, namely by distributing questionnaires in the form of G-forms to target respondents. Then the samples obtained were processed with a data processing system, namely Smart PLS, the total respondents who filled out the questionnaire were 107 people. After processing and testing the data, the results of this research indicate that work interest affects work readiness with positive significance and internship programs affect work readiness with positive significance, so that the hypothesis in this research are valid because both exogenous variables affect endogenous variables.